Regioselective molybdenum-catalyzed allylic substitution of tertiary allylic electrophiles: methodology development and applications - Salman, Muhammad; Xu, Yaoyao; Khan, Shahid; Zhang, Junjie; Khan, Ajmal (Chemical science (Cambridge), 2020)
The first molybdenum-catalyzed allylic sulfonylation of tertiary allylic electrophiles is described. The method employs a readily accessible catalyst (Mo(CO) 6 /2,2′-bipyridine, both are commercially available) and represents the first example of the use of a group 6 transition metal-catalyst for allylic sulfonylation of substituted tertiary allylic electrophiles to form carbon-sulfur bonds. This atom economic and operationally simple methodology is characterized by its relatively mild conditions, wide substrate scope, and excellent regioselectivity profile, thus unlocking a new platform to forge sulfone moieties, even in the context of late-stage functionalization and providing ample opportunities for further derivatization through traditional Suzuki cross-coupling reactions. The first general example of Mo-catalyzed allylic sulfonylation of tertiary allylic electrophile provides an efficient way to forge sulfone moieties, and providing ample opportunities for further transformation through traditional Suzuki cross-coupling.